Perancangan Produk Mesin Uji Metalografi Menggunakan Metode Quality Function Deployment (QFD): Metallographic Testing Machine Product Design Using Quality Function Deployment (QFD) Method - Rizky Nugroho; Handi; Yusrizal; Didik Sugiyanto (Universitas Muhammadiyah PROF. DR. HAMKA Fakultas Teknik – Program Studi Teknik Mesin, 2022)
Testing of the tool is carried out to find out whether the product is in accordance with the purpose of reducing the risk of physical disturbance or discomfort when testing the tool. Product evaluation is carried out by testing the product to users in metallographic testing equipment carried out by students of the Engineering Department so that the desired results are actually obtained. From each QFD analysis for each consumer need, what is considered very important is the frame material that is strong but has a light weight, the highest percentage difficulty level is in the table frame section 25%, the importance level is in the table frame section 33%, and the estimated costs are on the tool frame parts 50%